AquaShell Paver: Ecofriendly Paving Using Super Absorbent Polymer (SAP) and Eggshells - KAMARUDDIN, DIAN; Zailaini, Aizatul Umairah; Lokman Hakim, Muhammad Amin Afiq; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2026)
Urban development has lead to increased use of impermeable materials such as concrete and asphalt, causing significant environmental challenges including urban flooding, reduced groundwater recharge, and elevated carbon emissions. This study introduces an innovative and eco-friendly paving brick named AquaShell Paver Brick, which incorporates eggshell powder (ESP) and superabsorbent polymer (SAP) into conventional brick mixtures to address these issues. Eggshell powder, a calcium carbonate-rich waste material, partially replaces cement to reduce cement consumption and environmental impact. Meanwhile, SAP is added in small quantities to enhance moisture retention during curing, promoting better hydration and durability. The research evaluates the effects of varying ESP and SAP contents on the compressive strength and water absorption of the bricks, as well as the impact of different curing methods on structural integrity. Experimental results indicate that incorporating ESP obtain 38.17MPa and SAP improves strength and permeability compared to traditional bricks, although the combination of both additives requires careful curing to avoid strength loss due to excessive internal moisture. The study concludes that AquaShell Paver Bricks offer a sustainable alternative for urban infrastructure by improving water management, reducing waste, and lowering carbon footprint, aligning with goals of greener urban development.